2002
DOI: 10.1126/science.1070790
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Different Chromatin States of Autosomes and X Chromosomes in the Germ Line of C. elegans

Abstract: The Maternal-Effect Sterile (MES) proteins are essential for germline viability in Caenorhabditis elegans. Here, we report that MES-4, a SET-domain protein, binds to the autosomes but not to the X chromosomes. MES-2, MES-3, and MES-6 are required to exclude MES-4 and markers of active chromatin from the X chromosomes. These findings strengthen the emerging view that in the C. elegans germ line, the X chromosomes differ in chromatin state from the autosomes and are generally silenced. We propose that all four M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
134
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 25 publications
7
134
0
Order By: Relevance
“…Our analysis might be identifying those genes. Second, the X chromosomes of Drosophila and other animals become precociously condensed and inactivated in spermatocytes (11)(12)(13)(14). If X-chromosome inactivation occurs early enough to alter steady-state transcript levels in spermatocytes, then this effect could explain the underrepresentation we observe.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Our analysis might be identifying those genes. Second, the X chromosomes of Drosophila and other animals become precociously condensed and inactivated in spermatocytes (11)(12)(13)(14). If X-chromosome inactivation occurs early enough to alter steady-state transcript levels in spermatocytes, then this effect could explain the underrepresentation we observe.…”
mentioning
confidence: 68%
“…Indeed, in the only full-genome study of chromosomal bias to date, it was shown that C. elegans has essentially no X-chromosome genes showing male-biased germ line-restricted expression (15). This correlates with an altered chromatin state in those germ cells (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have provided empirical support for MSCI in a variety of species, including mammals (Richler et al, 1992;Handel et al, 1994;Turner, 2007), Caenorhabditis elegans (Fong et al, 2002;Kelly et al, 2002) and D. melanogaster (Hense et al, 2007;Vibranovski et al, 2009a). However, there is currently debate regarding the extent of X-linked germline expression silencing in Drosophila and whether it occurs through the same mechanism described as MSCI in other taxa.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we took advantage of the fact that the X chromosome in the germ cells of C. elegans is mostly transcriptionally silent. [14][15][16] If ZGA was triggering damage, we reasoned, then we would expect RAD-51 foci to form on the transcriptionally active autosomes, but rarely on the transcriptionally silenced X chromosomes. Using antibodies to differentiate between the autosomes and the X chromosomes, we found that in 98% of the nuclei scored, RAD-51 foci exclusively formed on the autosomes and not on the X chromosomes.…”
Section: Dna Damage Arises In Z2/z3 In a Nutrient-dependent Mannermentioning
confidence: 99%